Controversies of the Mai 68 Opera in Philosophical Contexts of Actual Opera Production - Cseres Jozef (Slovenské divadlo)
In his paper, the author reveals the poetical controversies of the Mai 68 opera (2008) by Petr Kofroň, Zdenek Plachý and Jiří Šimáček as well as its controversial reception by Czech opera critics. Comparing the poetical principles of the mentioned authors with those applied in stage works by Morton Feldman, Martin Burlas and John Zorn, and arguing with the philosophical concepts of Gilles Deleuze and Félix Guattari and actual concepts of postmodern aesthetics, he outlines the poetical features of current opera production in the context of actual philosophical thought and intermedia aesthetics. In this broader framework, in spite of some defects in staging, he considers Mai 68 a very real and influential contribution to the opera world in Czech Republic and Slovakia, comparable with the contemporary opera works worldwide.